Sulbactam Protects Hippocampal Neurons Against Oxygen-Glucose Deprivation by Up-Regulating Astrocytic GLT-1 via p38 MAPK Signal Pathway - Qi, Jie; Xian, Xiao-Hui; Li, Li; Zhang, Min; Hu, Yu-Yan; Zhang, Jing-Ge; Li, Wen-Bin (Frontiers in Molecular Neuroscience, 2018)
Sulbactam is an atypical β-lactam medication and reported to be neuroprotective by up-regulating GLT-1 in rats. The present study was undertaken to study the role of p38 MAPK signal pathway in sulbactam induced up-regulation of glial glutamate transporter-1(GLT-1) expression in astrocytes and anti-ischemic effect. Neuron-astrocyte co-cultures and astrocyte cultures from neonatal Wistar rats were used. Cerebral ischemia was mimicked by oxygen-glucose deprivation(OGD). Hoechst/propidium iodide double fluorescence staining and 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide assay were used to evaluate neuronal death and cell viability, respectively. Immunocytochemistry and Western blot were used to detect protein expressions. Sulbactam pre-incubation significantly and dose-dependently prevented neuronal death and decline in cell viability induced by OGD in neuron-astrocyte co-cultures, and upregulated GLT-1 expression in astrocyte cultures endured OGD, which suggested that sulbactam might protect neurons against OGD by up-regulating astrocytic GLT-1 expression. It was further shown that the phosphorylated-p38 MAPK expression in astrocytes was up-regulated after the sulbactam pre-incubation and this up-regulation was moderate in amplitude. Especially, the time course of the up-regulation of phosphorylated-p38 MAPK was obviously earlier than that of GLT-1, which suggested possibility that p38 MAPK might be an upstream signal for GLT-1 up-regulation induced by sulbactam. We further found that SB203580, the specific inhibitor of p38 MAPK, dose-dependently inhibited the GLT-1 up-regulation induced by sulbactam either in non- or OGD-treated astrocytes and the protective effect of sulbactam on co-cultured neurons against OGD. Taken together, it might be concluded that sulbactam protects cerebral neurons against OGD by up-regulating astrocytic GLT-1 expression via p38 MAPK signal pathway. Key words: sulbactam; p38 MAPK; GLT-1; astrocyte; OGD; neuron-astrocyte co-culture; astrocyte culture